Spiritualitas Perempuan Dalam Al-Qur'an - Mustaqim, Abdul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
The study of women's spirituality is one of the interesting themes in gender issues as it provokes controversies. There are doubting questions and negative perception about women's spirituality. There are subtle mixtures between mythology and theological argument that portray women's failure to attain spiritual power. By referring to the Qur'an, -the ultimate source of values for Muslims, by way of employing thematic methods of interpretation, the author argues that contrary to the negative image spread about women's spirituality, the Qur'an states that women and men have been bestowed equal potency to cultivate their utmost spirituality and appreciate them for maintaining and improving their spiritual purity and strength. The Qur'an highlights good stories about women's spirtuality; how their participation in advancing spiritual values is significant to build peaceful civilization based on belief in Unity of God, good deeds and belief in the Hereafter. Furthermore, the author points out that negative images of women's spirituality have root from hadits which are textually and partially understood, as well as mixed and coloured with stories from biblical mythology.